2009
DOI: 10.1103/physrevd.79.084028
|View full text |Cite
|
Sign up to set email alerts
|

Positive small-vacuum-region gravitational-energy expressions

Abstract: We construct an infinite number of new holonomic quasi-local gravitational energy-momentum density pseudotensors with good limits asymptotically and in small regions, both materially and in vacuum. For small vacuum regions they are all a positive multiple of the Bel-Robinson tensor and consequently have positive energy.PACS numbers: 04.20.Cv, 04.20.Fy The localization of energy for gravitating systems has been an important fundamental problem since before Einstein finalized his field equations (see [1]). In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It has been shown that a quadratic expression of these coordinates with the Bel-Robinson tensor as their coefficient appears naturally in the local conservation law for the matter energy-momentum tensor [327]; the Bel-Robinson tensor can be recovered as some ‘double gradient’ of a special combination of the Einstein and the Landau-Lifshitz pseudotensors [170]; Møller’s tetrad expression, as well as certain combinations of several other classical pseudotensors, yield the Bel-Robinson tensor [473, 470, 471]. In the presence of some non-dynamical (background) metric a 11-parameter family of combinations of the classical pseudotensors exists, which, in vacuum, yields the Bel-Robinson tensor [472, 474]. (For this kind of investigation see also [465, 468, 466, 467, 469]).…”
Section: Tools To Construct and Analyze Quasi-local Quantitiesmentioning
confidence: 99%
“…It has been shown that a quadratic expression of these coordinates with the Bel-Robinson tensor as their coefficient appears naturally in the local conservation law for the matter energy-momentum tensor [327]; the Bel-Robinson tensor can be recovered as some ‘double gradient’ of a special combination of the Einstein and the Landau-Lifshitz pseudotensors [170]; Møller’s tetrad expression, as well as certain combinations of several other classical pseudotensors, yield the Bel-Robinson tensor [473, 470, 471]. In the presence of some non-dynamical (background) metric a 11-parameter family of combinations of the classical pseudotensors exists, which, in vacuum, yields the Bel-Robinson tensor [472, 474]. (For this kind of investigation see also [465, 468, 466, 467, 469]).…”
Section: Tools To Construct and Analyze Quasi-local Quantitiesmentioning
confidence: 99%
“…[11][12][13]). For Einstein's general relativity it was possible to infer a suitable orthonormal normal frame (see [14][15][16]) without needing all the machinery developed here.…”
Section: Applicationsmentioning
confidence: 97%
“…In accordance with (10,12,13), at a preselected point we can choose the frame and holonomic basis so that…”
Section: The Affine Casementioning
confidence: 99%
“…3 But none of them gives positive energy for small vacuum regions [15]. An 11-parameter set of new pseudotensor superpotentials with this desirable property was constructed by So [16].…”
Section: The Pseudotensorsmentioning
confidence: 99%